PE/VC sector in Poland between 2005 and 2008 - Wiesław Dębski (Contemporary Economics, 2010)
Polish sector of PE/VC has begun to develop intensively in the recent years. Especially it is noticeable in comparison to the Central and Eastern Europe region. The article presents conditions and law regulations concerning existence of VC in Poland and PE investments done in Poland in 2005-2008 as well. The article shows also possibilities of further development PE/VC in Poland and their influence on economy.
Keywords: 330